Progress in muscle research through the international congress of neuromuscular diseases (ICNMD): a narrative review - Corrado Angelini (European Journal of Translational Myology, 2023)
Progress in muscle research has been through different phases over the past decades. Here are reviewed the advances presented at the International Congresses of Neuromuscular Diseases (ICNMD). In the ‘60 to ‘80 muscle physiology and interpretations of muscle biopsy were the major focuses, diagnosis of muscle disorders was advanced utilizing histochemical, and ultrastructural techniques, and the focus of first to IVth ICNMD was prevention and Muscle Disorders classification as major issues. After that from ‘80 to 2000 muscle neuromuscular junction (NMJ) immunology, biochemistry, molecular biology , therapeutic trials, and genetics were the major developments and represented the focus of research in following ICNMD from the Vth to the Xth. From 2000 to 2020 personalized medicine,genotype-phenotype correlation, and the use of DNA/RNA profiling , Imaging was developed and represented substantial signs of progress that were presented in ICNMD XIth to XVIIth. The future is evolving toward a major involvement of the pharmaceutical industry with new drugs and gene-delivered therapy, the use of biomarkers and robotics as well as of artificial intelligence, both for interpreting morphology, DNA, and imaging diagnostic, and such developments will be reflected in research presented in future Congresses.